Effects of Aggressive Movies on Children’s Aggressive Behaviour - Amoah, Charles Agyei; Ampong, Emmanuel (International Journal of Scientific Research and Management (IJSRM), 2020)
This study was about effects of aggressive movies on children’s aggressive behaviour. Forty (40) pupils were randomly selected from Korle Abansoro Primary School, Koforidua, Eastern Ghana, to participate in the study. An adapted version of peer nomination instrument for aggression designed by Crick & Grotpeter in 1995 was used to acquire the data. Half the participants watched an aggressive movie while the other half watched non-aggressive movie for thirty minutes each after which the participants were assessed using the aggressive behavioral checklist or scale. The independent ‘t’ test was used to analyze the results. Two of the hypotheses were confirmed while the other two were rejected. This indicated that children who watched an aggressive movie exhibited more aggressive behavior than children who watched non-aggressive movie and males were not more aggressive than females. Two of the findings were consistent with previous findings. The implication of these results was discussed.